Retraction Note to "Numerical Solution to Unsteady One-Dimensional Convection-Diffusion Problems Using Compact Difference Schemes Combined with Runge-Kutta Methods" [Contemporary Mathematics, Volume 2 Issue 4 (2021) 399-408] (Contemporary Mathematics, 2022)
The Editor-in-Chief and the publisher have retracted the following article:Zhu Z, Chen J. Numerical Solution to Unsteady One-Dimensional Convection-Diffusion Problems Using CompactDifference Schemes Combined with Runge-Kutta Methods. Contemporary Mathematics. 2021 Nov. 18; 2(4): 399-408.DOI: https://doi.org/10.37256/cm.2420211167.The above article has been retracted as a result of an article with a significant overlap in content having been published in the Universal Journal of Physics Research on November 5, 2021 as:Chen, J., & Zhu, Z. (2021). Compact Difference Schemes Combined with Runge-Kutta Methods for SolvingUnsteady Convection-Diffusion Problems. Universal Journal of Physics Research, 1(1), 1-10.DOI: https://doi.org/10.31586/ujpr.2022.155.This decision is made upon our policy on publishing ethics and the COPE guidelines.